Quality of life in patients with advanced epithelial ovarian cancer (EOC) randomized to maintenance pazopanib or placebo after first-line chemotherapy in the AGO-OVAR 16 trial. Measuring what matters—patient-centered end points in trials of maintenance therapy. (18th December 2017) - Friedlander, M; Rau, J; Lee, C K; Meier, W; Lesoin, A; Kim, J -W; Poveda, A; Buck, M; Scambia, G; Shimada, M; Hilpert, F; King, M T; et al.
Abstract: Background: Health-related quality of life (HRQoL) was a secondary end point in AGO-OVAR 16, which randomized 940 patients with EOC after first-line chemotherapy to maintenance pazopanib (PZ) or placebo (P). Additional post hoc analyses were carried out to investigate additional patient-centered end points. Patients and methods: HRQoL was measured with EORTC-QLQ-C30, QLQ-OV28 and EQ-5D-3L. Pre-specified end points included mean differences in HRQoL between treatment arms. Exploratory analyses included quality-adjusted progression-free survival (QAPFS), impact of specific symptoms and progressive disease (PD) on HRQoL and time to second-line chemotherapy. The objective was to provide clinical perspective to the significant median PFS gain of 5.6 months with PZ. Results: There were statistically significant differences between PZ and P in QLQ-C30 global health status [5.5 points; 95% confidence interval (CI), 0.7–10.4, P = 0.024] from baseline to 25 months, but not EQ-5D-3L (0.018 points; 95% CI − 0.033 to 0.069, P = 0.485). The impact of diarrhea was captured in QLQ-OV28 Abdominal/GI-Symptoms scale (8.1 points; 95% CI 3.6–12.5, P = 0.001). QAPFS was 386 days (95% CI 366–404 days) with PZ versus 359 days (95% CI 338–379 days) with placebo ( P = 0.052). PD was associated with a decline in HRQoL ( P < 0.0001). Median time to second-line chemotherapy was 19.7 months with PZ and 15.0 months with P [hazard ratio (HR) 0.72, 95% CI 0.69–0.86, P = 0.0001]. Conclusions: There were small to no significant mean score differences in global HRQoL and EQ5D-3L between PZ and placebo, respectively, despite the increased toxicity of PZ. Exploratory end points including QAPFS, impact of specific symptoms on HRQoL during treatment and at PD help place the PFS gain with PZ in context and interpret the results. Additional patient-centered end points should be considered in trials of maintenance therapy in EOC beyond mean differences in HRQoL scores alone, to support the benefit to patients of prolongation of PFS. Clinical Trials Registration Number: NCT00866697